Reconfigurable Cell-Array (RCA) Based Computer System with Cell Specialization - Bilenko, Anatoliy; Sitnikov, Valeriy (ТНЕУ, 2012)
Reconfigurable system based on cell specialization of reconfigurable cell-array computer system is presented. Analysis of specialized reconfigurable cell-array hardware and methods of specialized cell inclusion are given.
Keywords: architecture of computer systems; reconfigurable systems